Subdural hematoma expansion in relation to measured mean and peak systolic blood pressure: A retrospective analysis - Plowman, Keegan; Lindner, David; Valle-Giler, Edison; Ashkin, Alex; Bass, Jessica; Ruthman, Carl (Frontiers in Neurology, 2022)
Objective Subdural hematomas (SDH) account for an estimated 5 to 25% of intracranial hemorrhages. Acute SDH occur secondary to rupture of the bridging veins leading to blood collecting within the dural space. Risk factors associated with SDH expansion are well documented, however, there are no established guidelines regarding blood pressure goals in the management of acute SDH. This study aims to retrospectively evaluate if uncontrolled blood pressure within the first 24 h of hospitalization in patients with acute SDH is linked to hematoma expansion as determined by serial CT imaging. Methods A single center, retrospective study looked at 1,083 patients with acute SDH, predominantly above age 65. Of these, 469 patients met the inclusion criteria. Blood pressure was measured during the first 24 h of admission along with PT, INR, platelets, blood alcohol level, anticoagulation use and antiplatelet use. Follow-up CT performed within the first 24 h was compared to the initial CT to determine the presence of hematoma expansion. Mean systolic blood pressure (SBP), peak SBP, discharge disposition, length of stay and in hospital mortality were evaluated. Results We found that patients with mean SBP <140 in the first 24 h of admission had a lower rate of hematoma expansion than those with SBP > 140. Patients with peak SBP > 200 had an increased frequency of hematoma expansion with the largest effect seen in patients with SBP > 220. Other risk factors did not contribute to hematoma expansion. Conclusions These results suggest that blood pressure is an important factor to consider when treating patients with SDH with medical management. Blood pressure management should be considered in addition to serial neurological exams, repeat radiological imaging, seizure prophylaxis and reversal of anticoagulation.